To the question about settlement problems of chemical potential in the alloyed semiconductor crystals - Буджак, Ярослав Степанович; Зуб, Ольга Василівна (Eastern-European Journal of Enterprise Technologies, 2012)
The paper describe classical equation of neutrality semiconductor crystals. Happens to its functional analysis and showing the impact of electronic processes in a crystal at its root chemical potential carriers